2012
DOI: 10.1097/olq.0b013e318235b3c6
|View full text |Cite
|
Sign up to set email alerts
|

Does the Internet Represent a Sexual Health Risk Environment for Young People?

Abstract: This study examined sexual risk behaviors/outcomes among college students with online partners only, offline partners only, and both online/offline partners. Students with both online/offline partners were more likely to report sexually transmitted diseases, unintended pregnancy, and more vaginal/oral sex partners. Sex with online partners was not riskier than sex with offline partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
12
3
Order By: Relevance
“…We found a high prevalence, compared with previous studies among heterosexual young people with estimates of 6%–33%,6 10 14 24 25 varying considerably with how participants were recruited. Although our questionnaire did not ask the specific context and online meeting venue for internet-partners, both this study and previous research show that not all adolescents reporting internet-partners may explicitly have sought sexual partners online 6 14. A recent study in a teen clinic in Florida among 273 participants (90% girls) found that four of five participants reporting internet-partners had met that partner on a social as opposed to sexual networking site, suggesting an initial social reason 6…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…We found a high prevalence, compared with previous studies among heterosexual young people with estimates of 6%–33%,6 10 14 24 25 varying considerably with how participants were recruited. Although our questionnaire did not ask the specific context and online meeting venue for internet-partners, both this study and previous research show that not all adolescents reporting internet-partners may explicitly have sought sexual partners online 6 14. A recent study in a teen clinic in Florida among 273 participants (90% girls) found that four of five participants reporting internet-partners had met that partner on a social as opposed to sexual networking site, suggesting an initial social reason 6…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, our finding that boys (but not girls) reporting internet-partners (ever) had higher chlamydia prevalence than those reporting only offline partners may not contradict these results. Two recent studies on college students and MSM, respectively, found significantly more risk behaviours among individuals reporting both offline partners and internet-partners, suggesting that among those engaging in risky sexual behaviour, the internet was an additional source of sexual partners,5 14 but this could not be assessed in our data.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…However, few studies have been conducted on their risky sexual behaviours and they showed mixed findings. One study found that internet sex seekers reported more sexual partners, more anal sex and more exposure to partners known to be HIV positive in the past 12 months than those not seeking sex online,1 whereas another study showed no increase in unprotected vaginal or anal sex at first sexual experience with an online than with an offline partner 10…”
Section: Introductionmentioning
confidence: 99%